Avaliação diagnóstica de ações de nivelamento para alunos cotistas e não cotistas – estudo de caso em Universidade Pública Estadual - Barros, Aluizio Dalla Vecchia (2021)
The presentstudy aimsto investigate the effectiveness of the leveling actionsregarding the academic performance of quota holders and non- quota holders of Civil Engineering, Electrical Engineering and Mathematics courses, which comprise the Faculty of Exact and Technological Sciences (FACET) of the State University of Mato Grosso (UNEMAT), Sinop Campus. Developed as a pedagogical proposal, these leveling actions are a response to incoming students who demonstrate learning difficulties in Basic Mathematics content, which are part of the curricular basis of elementary and secondary education, and which support the undergraduate subjects. The theoretical framework presentsthe concept of affirmative action, as well asit’s application in selective processes for entry into Higher Education, as well as the historical path of Affirmative Action in Brazil. In addition, it contextualizes the reasons that guided the adoption of measures to correct the learning deficit presented by new students entering higher education. It is a descriptive-explanatory type of research with quali-quantitative approach, case study and expost-facto. The method used is the inductive method with cross-section from 2015 to 2019. The population consists of 960 students and 3 teachers of the leveling disciplines and the sample corresponds to the return rate of the questionnaires sent online. The data collection instrument is the semi-structured electronic questionnaire aimed at incoming students from 2015. Initially, documental analysis will be performed in search of information regarding the Coefficient of Academic Performance (CRA) of Students, Approval, Failure and Evasion. Subsequently, at the end of the research, it isintended, with the data analysis, to point out a possible contribution of the leveling actions to a better academic performance in terms of school performance, as well as their impact on the approval, self-esteem and development of a more significant and autonomous learning of mathematics, capable of contributing to progress in the next levels of education.